Sewage treatment of one poultry profit center using Moringa oleifera - Moreno-Rodriguez, Diana (2023)
The poultry industry is growing annually due to high commercial demand. This activity needs a high amount of water for its processes, which after being used must be treated properly to be discharged into the sewer. For this reason, we have investigated the potential of moringa seeds to treat wastewater from a Poultry Profit Center. After processing seeds, the extract obtained was tested, taking turbidity as an initial indicator to determine the optimal dosage. Four samples were then analyzed in a certified laboratory. Of these, one sample contained untreated water and three samples contained water treated with moringa extract at different concentrations (10mg/l, 15mg/l, and 20mg/l), all from the pools of the Poultry Profit Center; to evaluate the efficiency of the formulation in the removal of BOD5, COD, SST, coliforms, ammonia, oils, and fats. The results showed high removal efficiency, indicating improved water quality.